Corrosion of organosilane coated Mg4Y alloy in sodium chloride solution evaluated by impedance spectroscopy and pH changes - Doepke, Amos; Xue, Dingchuan; Yun, Yeoheung; Vanooij, William J.; Brian Halsall, H.; Heineman, William R. (Electrochimica acta, 2012)
Electrochemical impedance spectroscopy (EIS), open circuit potential and pH changes were used to examine the corrosion of magnesium 4% yttrium alloy (Mg4Y) with and without a silane-epoxy-coating (SEC) in a stirred 0.154M NaCl solution at 37°C. For a good quality SEC we find a relatively low non-Faradaic resistance of 266Ωcm2. The quality of the SEC was affected by the curing temperature. In this article we compare the electrochemical measurements taken during corrosion of bare Mg4Y, Mg4Y with a SEC that remained intact, and a SEC that did not protect the Mg from corrosion.